Oral health knowledge, behaviour and practices among school children in Qatar - Mohammed Sultan Al-Darwish (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of this study was to assess the oral health knowledge behaviour and practices among school children in Qatar. Materials and Methods: A cross-sectional study was carried out in Qatar from October 2011 to April 2012. A total of 2200 school children aged 12-14 years were approached from 16 schools of different areas. The information about oral health knowledge and sources of information was obtained through a self-administrated questionnaire. Data analyses were performed. Results: The overall response rate was (96%). Only (25.8%) of children reported a high level of oral health knowledge. After each meal, tooth brushing was observed by a very low percentage of children (3.7%). About 44.6% of children recognized dental floss as a cleaning device for between the teeth. A large number of children (32.5%) thought incorrectly that one must visit the dentist only in case of pain. A great majority was not aware of cariogenic potential of soft drinks (39%) and sweetened milk (97.8%). Less than half (38.9%) of children actually had heard about fluoride. Only (16.8%) correctly answered the question about sign of tooth decay. Slightly, less than half (48.4%) could not define the meaning of plaque. Parents were the most popular (69.1%), source of oral health information for the children. Conclusion: The oral health knowledge in Qatar is below the satisfactory level. Parents were the most popular source of oral health knowledge for the children followed by dentists, school teachers, and media.